Une écologie de l'alimentation - Bricas, Nicolas; Conaré, Damien; Walser, Marie (éditions Quae, 2021)
Rethinking our food is rethinking our societies. Because to share a meal and even to do his races are a means of connecting with others. The way we eat builds our health. Our agricultural production methods shape our landscapes and define our place in nature. Managing resources to produce, process and distribute food is the foundation of our economies. Our edible registers, our cuisine and our table manners tell our cultures. Last but not least, eating is a pleasure ... It is by recognizing all these dimensions with equal importance that this book addresses contemporary issues of food. The proposal for an ecology of food is anchored in the double register of a science of relationships and of political commitment. Such an approach makes it possible to revisit, sometimes unexpectedly, the watchwords of sustainable food. It also aims to nurture citizen, public and private initiatives engaged in the transformation of food systems. Between an expert essay and an illustrated story of examples from around the world, this book is aimed at both professionals and a general public curious about sustainable food issues.